Individual Social Capital and Physical Activity in Riley County, Kansas - Pluta, David (My University, 2018)
I completed my Applied Practice experience with the Flint Hills Wellness Coalition, under the direction of Jared Tremblay, chair of the active transportation workgroup. The Flint Hills Wellness Coalition is an organization whose mission is to create a healthier and more equitable community in Riley County, KS. The organization promotes collaboration between residents and groups within the community and seeks to impact change at multiple levels: policy, systems, environment, and individuals. The Flint Hills Wellness Coalition has various workgroups which focus their efforts on a particular issue: nutrition, active transportation, mental health, or access & coordination of services.
Keywords: physical activity; individual social capital